Search for Extended Sources of Neutrino Emission in the Galactic Plane with IceCube - R. Abbasi; M. Ackermann; J. Adams; S. K. Agarwalla; J. A. Aguilar; M. Ahlers; J. M. Alameddine; N. M. Amin; K. Andeen; G. Anton; C. Argüelles; Y. Ashida; et al. (The Astrophysical Journal, 2023)
The Galactic plane, harboring a diffuse neutrino flux, is a particularly interesting target in which to study potential cosmic-ray acceleration sites. Recent gamma-ray observations by HAWC and LHAASO have presented evidence for multiple Galactic sources that exhibit a spatially extended morphology and have energy spectra continuing beyond 100 TeV. A fraction of such emission could be produced by interactions of accelerated hadronic cosmic rays, resulting in an excess of high-energy neutrinos clustered near these regions. Using 10 years of IceCube data comprising track-like events that originate from charged-current muon neutrino interactions, we perform a dedicated search for extended neutrino sources in the Galaxy. We find no evidence for time-integrated neutrino emission from the potential extended sources studied in the Galactic plane. The most significant location, at 2.6 σ post-trials, is a 1.°7 sized region coincident with the unidentified TeV gamma-ray source 3HWC J1951+266. We provide strong constraints on hadronic emission from several regions in the galaxy.